Bridging the gap between goal intentions and actions: a systematic review in patient populations. (7th July 2014) - Kersten, Paula; McCambridge, Alana; M. Kayes, Nicola; Theadom, Alice; McPherson, Kathryn M.
Abstract: Purpose : To evaluate the evidence for the effectiveness of if-then implementation intentions ( if-then plans) in adult patient populations. Outcomes of interest included adherence, goal pursuit and physical health outcomes. Methods : Keywords were used to search electronic databases without date or language restrictions (up to 30 April 2014). Studies were included if they (1) concerned a patient population; (2) used if-then plans as a sole intervention or as part of treatment, therapy or rehabilitation; (3) if they were randomised controlled trials. The PEDro scale was used to evaluate study quality. Guidance as set out by the Cochrane Collaboration was used. Two reviewers independently extracted data, discrepancies were discussed and if required referred to a third reviewer. Results : In total, 18 of the 2141 articles were identified as potentially relevant and four studies of people with epilepsy, chronic back pain, stroke and obesity met the inclusion criteria. People who form if-then plans achieved better outcomes on epilepsy and stroke medication adherence and physical capacity than controls. Conclusions : Of the four studies that used an if-then plan, only one (people with epilepsy) looked at the intervention as a stand-alone strategy. Further research needs to explore if this simple approach improves rehabilitation outcomes and is a helpful and feasible strategy for people experiencing disabilities. Implications for Rehabilitation: Steps involved in achieving goals, such as doing exercises or completing other goal related tasks, can be compromised for people with chronic health conditions particularly resulting from difficulties in self-regulating behaviour. If-then plans are implementation intention tools aimed at supporting people to deal more effectively with self-regulatory problems that might undermine goal striving and goal attainment, and have been found to be effective in health promotion and health behaviour change. This systematic literature review identified four studies completed with patient populations, with three demonstrating effectiveness. If-then plans provide an opportunity for clinicians to develop better ways of implementing rehabilitation.